Research on formation mechanism and optimization method of surface waviness of TC4 blisk blade. (March 2019) - Wu, Dongbo; Wang, Hui; Zhang, Kaiyao; Lin, Xiaojun
Abstract: Blisk blade surface waviness directly affects the mechanical behavior of aero-engine. This paper studies formation mechanism and optimization method in the entire CNC machining process of blisk blade. Firstly, flexible CNC adaptive polishing and its vibration characteristics were analyzed. Secondly, blisk blade CNC machining process and the formation and elimination of surface waviness were analyzed by 3D contour analysis and spectrum analysis based on wavelet analysis, and relationship between polishing vibration and surface waviness was analyzed, and proposed that surface waviness should be optimized in precision milling stage. Thirdly, an empirical model of surface waviness to milling parameters was established based on orthogonal experiment, and analyzed based on response surface and sensitivity analysis method. Finally, optimal interval and value of milling parameters were selected, and the feasibility of the proposed method was verified by cutting experiments. The results show that flexible CNC adaptive polishing produces intermittent forced vibration of high frequency and the relationship between vibration frequency and spindle speed is linear, and is a stable polishing process without "excessive-polishing" and "deficient-polishing" phenomenon. Flexible CNC adaptive polishing only changes high frequency surface profile, rather than low frequency surface waviness. Milling surface waviness can be improved by reasonably controlling milling process parameters, and the decrease of surface waviness can improve efficiency of subsequent micro polishing processing. Flexible CNC adaptive polishing combined with the optimized milling parameters will achieve high-performance manufacturing of blisk blade.